2018
DOI: 10.2214/ajr.18.19620
|View full text |Cite
|
Sign up to set email alerts
|

Does Extended PET Acquisition in PET/MRI Rectal Cancer Staging Improve Results?

Abstract: Longer PET acquisition times during PET/MRI for rectal cancer increases the number of FDG-avid lymph nodes detected without increasing scan time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
22
1
1
Order By: Relevance
“…Attempts to develop improved accuracy are desirable as the assessment of N-stage remains challenging in rectal cancer [ 2 , 3 , 5 8 ]. In a recent study, Baily et al show that PET/MRI identified 94 hypermetabolic nodal structures presumed to be lymph nodes in 29 patients with rectal cancer, where approximately 61% of the metabolically abnormal lymph nodes had a size of 5 mm or less [ 20 ]. While the study lacked histopathological matching, the findings suggest that the assessment of mesorectal nodal structures could be facilitated with the aid of the metabolic information from FDG-PET/MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to develop improved accuracy are desirable as the assessment of N-stage remains challenging in rectal cancer [ 2 , 3 , 5 8 ]. In a recent study, Baily et al show that PET/MRI identified 94 hypermetabolic nodal structures presumed to be lymph nodes in 29 patients with rectal cancer, where approximately 61% of the metabolically abnormal lymph nodes had a size of 5 mm or less [ 20 ]. While the study lacked histopathological matching, the findings suggest that the assessment of mesorectal nodal structures could be facilitated with the aid of the metabolic information from FDG-PET/MRI.…”
Section: Discussionmentioning
confidence: 99%
“…in the head-and-neck region, brain, pelvis, breast, and in paediatric oncology [ 13 , 14 ]. Few studies have evaluated the role of 18 F-fluoro-2-deoxy-D-glucose (FDG) PET/MRI in colorectal cancer and even fewer in patients with primary rectal cancer [ 15 20 ]. None of these studies have matched individual nodal structures anatomically with a histopathological analysis, which is of importance for a valid comparison of imaging and histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, an association between extended PET acquisition time and increased number of false positives has not been reported previously. A single study that considered the effect of extended PET acquisition time during PET/MRI staging of rectal cancer reported a greater lymph node detection rate for 15‐minute versus 3‐minute acquisitions but the lack of a reference standard prevented assessment of false‐positive rates . The prevalence of inflammatory lymph nodes relative to malignancy at staging is likely to be low in comparison to post‐treatment imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of numerous rectal cancer postoperative bed morphological changes offer a great challenge during serial follow-up of the rectal cancer post-operative patients; similar morphological patterns are noted in the normal post-operative fields as well as the evolving residual/recurrent neoplastic process. Differentiation of post-therapeutic alterations attributable to scarring, inflammation, and necrosis from residual or recurrent tumors poses significant problems for CT [9].…”
Section: Discussionmentioning
confidence: 99%